(untitled) (The Journal of Plant Protection Sciences, 2023)
Insect response to rise in atmospheric temperature and carbon dioxide differ from one region to the other. The lat est assessment report from the Intergovernmental Panel on Climate Change (IPCC) predicts an increment in mean atmospheric temperature from 1.1 to 6.4°C toward the year 2100 with equally increasing atmospheric carbon diox ide (CO2). Such climatic changes could profoundly affect insect’s population on essential crops. This study was conducted during the 2010 and 2011 cropping season at the University of Abuja Teaching and Research Farm (Nigeria) in order to determine the impacts of climate change on the population of insects associated with cowpea production in the region. The result showed an increase in the number of taxa encountered on the cowpea field from 21 to 31 orders of insect in the 2010 and 2011 cropping seasons, respectively. Also, no significant difference was established in the forms of destructions recorded at the various growth stages of the cowpea plant in the two seasons. Therefore the advent of increased fauna on cowpea established in this study portrayed a need to find pos sible ways to reduce the emission of Greenhouse gases in the region in order to ameliorate the effects of induced global warming on cowpea production in the country and also provide effective control of the identified pest in order to maintain or stall resurgence.